La notion de modèle de discours appliquée à la traduction - Bocquet, Claude (Studia Romanica Posnaniensia, 2007)
The author makes an attempt at determining how much and to what an extent various types of discourse and their characteristics have, or should have, an influence on the process of translation. In the text it is shown in what way the medical discourse historically had an influence on the modern French in the field of economics. In order to draw conclusions concerning translation of this type of texts this kind of special French is compared with the German and Italian language of economics.